Platform work and labour legislation in India: Women’s engagement and the role of gender - Neha Arya; Abhishek Nemuri (Labour & Law Issues)
Focusing on India's digital platform economy, this study examines the gendered experiences of workers. We present a novel methodology to study the working conditions and key issues faced by platform workers in the beauty and personal services segments. Our data comprises 328 workers (both male and female) associated with two popular platforms in India. We find that most workers face issues such as algorithmic control, insufficient technical support, feedback mechanism, safety protocols, and cost concerns. The paper also draws attention to existing provisions applicable to female workers and recent legislative developments related to platform work in India. Through detailed analysis of workers’ reviews and experiences, this paper calls for a calibrated alignment of India's legal framework with the swiftly evolving technological landscapes globally. In this, it emphasizes gender inclusivity to ensure equitable labour market opportunities.